Enhancing Pancasila Education: The Role of Learning Interest and Digital Literacy in Shaping Gen Z Learning Patterns - Nurholipah, Wahyu; Patmisari, Patmisari (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Study this aiming to know the influence interest learning and digital literacy towards pattern Gen Z learning in partial and simultaneous on the eyes Pancasila Education lessons. Methodology: Types of research methods used that is quantitative with design correlational. Research is used to test the hypothesis that has been submitted. Samples in the study totaling 268 partic-ipants in high school/vocational high school education in Surakarta City. Engineering data was collected through a distribution questionnaire with a points scale Likert as a tool meas-ure. The study used analysis regression multiple with the assistance of the SPSS version 27 program. Results: Research results show that 1) Interest in learning influential in a way partial to pattern Study with t- value 4.427 > t- table 1.969. 2) Digital literacy has an effect in a way partial to pat-tern study with t- t-value count 8.066 > t- t-table 1.969. 3) Interest in learning and digital literacy has marked significant F 0.000 <0.05 and the Adjusted R Square value is 0.332. This shows contribution to interest learning and digital literacy is 33.2% and the remaining 66.8% was influenced by other variables outside variables studied. Applications/Originality/Value: Based on the results, hypothesis interest learning and literacy digital has influenced in a way partial and simultaneous to pattern Gen Z learning on Pancasila Education lessons. This fills in emptiness in existing literature, regarding factors that influence pattern Study Gen Z in context Education Pancasila. Uniqueness study This located on the focus that is Gen Z, a combination of interest learning and digital literacy, as well as Education Pancasila. In gen-eral, overall, research can enrich understanding about the learning process of Gen Z and give implications for development of more educational programs relevant to Gen Z.